2018
DOI: 10.3390/ph11030066
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Lipopolysaccharide Increases Serotonin Metabolism in Both Medial Prefrontal Cortex and Nucleus Accumbens in Male Wild Type Rats, but Not in Serotonin Transporter Knockout Rats

Abstract: It is well known that bacterial lipopolysaccharides (LPS) both increases proinflammatory cytokines and produces sickness behavior, including fatigue and anhedonia (i.e., the inability to experience pleasure). Previously, we have shown that intraperitoneally (i.p.) administered LPS increased extracellular monoamine metabolite levels in the nucleus accumbens (NAc) and medial prefrontal cortex (mPFC), which was completely, or at least partly, prevented by pretreatment with a triple reuptake inhibitor that also bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
(76 reference statements)
1
13
0
Order By: Relevance
“…As expected, TNF-α inhibition with etanercept reduced this SERT availability [84]. More about immune activity and monoamine transporter function can be found in the present Special Issue of Pharmaceuticals [85].…”
Section: Discussionsupporting
confidence: 54%
“…As expected, TNF-α inhibition with etanercept reduced this SERT availability [84]. More about immune activity and monoamine transporter function can be found in the present Special Issue of Pharmaceuticals [85].…”
Section: Discussionsupporting
confidence: 54%
“…LPS also modulates serotonin metabolism, for example, activating the serotonin transporter (SERT) and, consequently, serotonin reuptake 61 , 62 . Similar effect was observed here for LPS + fluoxetine, lowering serotonin levels (vs. chronic stress, fluoxetine, EPA and LPS), and also affecting serotonin turnover.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, an intracerebroventricular injection of 10 mcg of 5-HT in the LPS-injected group reduced LPS-induced fever, plasma corticosterone, and plasma IL-6 release. Korte-Bouws et al [80] showed that LPS-induced 5-HT metabolism is significantly increased in both the Nucleus Accumbens (NAc) and Medial Prefrontal Cortex (mPFC) of homozygous (SERT+/+) male rats whereas this increase is partly or completely abolished in heterozygous (SERT+/-) or knockout (SERT-/-) male rats, respectively. The results of these studies suggested that bacterial LPS released by the intestine could interfere with the efficacy of drugs that act on the 5-HT receptor, potentially inducing adverse effects.…”
Section: Gut Motilitymentioning
confidence: 99%